The Influence and Feasibility of Therapeutic Exercise Videos at Home on the Functional Status of Post-COVID-19 Hospitalization - Wahyuni, Luh Karunia; Harini, Melinda; Sunarjo, Peggy; Ramadhany, Mellisya; Fitriana, Ika; Hidemi, Octaviany; Wijayanti, Indri; Nugraha, Boya; Tedjasukmana, Deddy; Tamin, Tirza Z (UI Scholars Hub, 2023)
The COVID-19 pandemic pushed physicians to modify conventional practices to reduce the exposure and risk of infection among patients and health workers. Telemedicine is one of the safest methods, and telerehabilitation could prevent the sequelae of COVID-19. A quasi-experimental study with randomized sampling without masking/blinding was conducted. The study was conducted from August 2021 to March 2022 at Hospital A in Pekanbaru, Hospital B in Jayapura, and Hospital C in Jakarta, Indonesia. A total of 27 patients were recruited and divided into control and intervention groups. The control group was given conventional education on therapeutic exercise at home, while the intervention group was shown educational videos about therapeutic exercise at home. The comparison of all functional outcomes between the two groups after the intervention showed a significant difference. The intervention group improved more than the control group, except for the fatigue severity scale. Most of the responses showed that this video was feasible and useful and did not need to be supervised by health workers. Therapeutic exercise educational videos can be an option to deliver rehabilitation programs for post-COVID-19 hospitalized patients.